Carl Jung: a life on the edge of reality with hypnagogia, hyperphantasia, and hallucinations - Incekara, Fatih; Blom, Jan Dirk (Frontiers in Psychology, 2024)
Whether the Swiss psychiatrist Carl Jung (1875–1961) became psychotic after his mid-thirties is much debated. His recently published Black Books, a seven-volume journal, reveal new insights into this debate. Based on a phenomenological analysis of his self-reports in these books and in other writings, we here identify several types of anomalous perceptual experiences: hypnagogic-hypnopompic experiences, hyperphantasia, hallucinations, personifications, and sensed presence. We argue that these experiences were not indicative of a psychotic disorder, but rather stemmed from extremely vivid mental imagery, or hyperphantasia, a condition Jung’s contemporaries and later biographers were unable to take into account because it had not yet been conceptualised. Recently, the degree of vividness of mental imagery and its potential to become indistinguishable from regular sense perception has been the subject of extensive studies. Unknowingly, Jung may have foreshadowed this line of research with his psychoanalytic concept of reality equivalence, i.e., the substitution of an external world for an inner mental reality that he encountered in individuals diagnosed with schizophrenia. There is a need for future research to investigate the possible role of hyperphantasia in psychotic experiences, but to Jung, psychosis was ‘a failure to contain and comprehend’ the content of one’s experiences in the context of one’s own life, whereas he himself did manage to put the content of his perceptual experiences into context, to find meaning in them, and to share them with others - to great acknowledgement and acclaim.